Labod pevec Cygnus cygnus - Kurillo, Jurij (Acrocephalus, 1995)
3 on 21st December 1994 as well as on 22nd and 29th January 1995 above and on the Sava river near Kranj
Keywords: Birds; Cerkniško jezero; Cygnus cygnus; labod pevec; Ornithology; ornitologija; ptiči; Slovenia; Slovenija